PENGARUH PENGETAHUAN, SIKAP DAN MOTIVASI TERHADAP KEPATUHAN STANDAR OPERASIONAL PROSEDUR PADA PEKERJA INDUSTRI - Bayu sela priyatna; Muhamad Fauzi; Wati Istikomah (SEKOLAH TINGGI ILMU KESEHATAN (STIKes) INDRAMAYU, 2022)
Every year accidents occur in the workplace which cause casualties, both minor and serious injuries. Compliance with the implementation of standard operating procedures is needed to minimize and protect workers from the risk of accidents in the workplace. Knowledge, attitudes and motivation are factors from the human component that affect workers. This study aims to determine the effect of knowledge, attitudes and motivation on standard operating procedures in industrial workers. This research method uses literature reviews by searching for articles through electronic media such as Google Scholar, Garuda Portal, Neliti, Microsoft Academia, and Open Knowledge Map. The keywords used to search for articles included standard operating procedures, knowledge, attitudes, motivation, motivation, knowledge, attitudes, motivation, compliance, standard operating procedures, and SOPs in selecting research articles using inclusion and exclusion criteria and journal analysis. The results of the study of the 9 articles of knowledge variables analyzed, there were 6 articles that had a relationship, 6 articles from the attitude variable, 4 of which had no relationship and 5 of the variable motivation articles, 3 of which had a relationship between knowledge and standard operating procedures. The knowledge and motivation conclusion variables have an influence on the operational guidelines of industrial workers, while the attitude variable has no influence on the standard operating procedures of industrial workers. Efforts are needed to increase knowledge and motivation for SOPs to prevent workplace accidents.